Patrulha multiagente de arestas - Valle, Aline Marques Del (2008)
This paper aims to develop a new multiagente algorithm called Multi_Agent_Ciclic_Edge_Walk, to patrol edges of dynamic Eulerians graphs that minimize the idleness of the edges making it more uniform. The algorithm is an extension of the Yanovski’s et. al. algorithm (2002). It also aims to establish metrics on the idleness measuring the performance of the algorithm which will be compare at with the Yanovski’s results and variation of then based on partition, called Multi_Agente_Partition_Edge_Walk. It was found that the proposed algorithm obtained better results with respect to the metric studied in this work.